Análisis del movimiento cinemático de un motor stirling tipo alfa aplicado al motor de una motocicleta - Manya Yuquilema, Héctor Geovanny (2016)
Shows a kinematic analysis of the alpha Stirling engine alpha, applied to motorcycle internal combustion engine in V to sixty degrees, has the purpose of this project. This analysis allows seeing the compatibility between both Stirling and internal combustion engine, determining the compatibility of the two types of engines before mentioned, will be designed with the necessary elements to make both kinematics. Five chapters is divide this document, as follow: All issues of kinematics mechanism synthesis: freedom grades, and general equations of velocity, acceleration, and position contains in the first chapter. Second chapter contains kinematic analysis of internal combustion engine, functioning principles, engine selection, calculated with graphical and algebraic methods, complemented with mathematical analysis software. Therefore the use of software such as: Matlab, Autodesk Inventor Professional 2016 and Working Model is essential. Third chapter deals with kinematic analysis of alpha Stirling engine, functioning principles, calculated with graphical and algebraic methods and complemented as second chapter with mathematical analysis programs to comparison with second chapter results. The kinematic analysis of the alpha Stirling engine is shown in the chapter three, it develops the principle of operation, analysis, graphical and algebraic methods. xviii In the fourth chapter, the design of the elements appears, so that the engine of internal combustion in V to sixty grades acquires the kinematics of the engine Stirling. Besides it presents the calculations of efforts and deformations. Finally in the fifth chapter the conclusion and recommendations of this work are presented.